1973
DOI: 10.1088/0029-5515/13/5/007
|View full text |Cite
|
Sign up to set email alerts
|

High-β plasma behaviour in a canted mirror

Abstract: A high-0 hot-electron plasma was studied in an asymmetric magnetic mirror device with a variable cant angle. The plasma was produced by microwave heating at a frequency corresponding to cold-electron-cyclotron resonance together with a higher frequency suitable for upper-off-resonance heating. The position of the high-0 plasma annulus was studied as a function of cant angle and was found to correspond approximately to the position of a midplane modulus-B contour. High-0 effects did modify the spatial location … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 7 publications
(15 reference statements)
0
22
0
Order By: Relevance
“…Some data on the former technique have been obtained in the Symmetric Tandem Mirror experiment at TRW Corporation (Redondo Beach, CA). Building on extensive earlier experience with electron rings in the ELMO [327] and the EBT [328] experiments at Oak Ridge, the TRW group has demonstrated the formation of stable hot-electron rings in their device [329]. Recently, the Phaedrus group in Wisconsin has shown that stability against gross modes in an otherwise MHD-unstable TM plasma can be achieved by the use of RF ponderomotive forces [330].…”
Section: Fig 82 Experimentally Determined Interchange Stability Limit...mentioning
confidence: 99%
“…Some data on the former technique have been obtained in the Symmetric Tandem Mirror experiment at TRW Corporation (Redondo Beach, CA). Building on extensive earlier experience with electron rings in the ELMO [327] and the EBT [328] experiments at Oak Ridge, the TRW group has demonstrated the formation of stable hot-electron rings in their device [329]. Recently, the Phaedrus group in Wisconsin has shown that stability against gross modes in an otherwise MHD-unstable TM plasma can be achieved by the use of RF ponderomotive forces [330].…”
Section: Fig 82 Experimentally Determined Interchange Stability Limit...mentioning
confidence: 99%
“…The EBT experiment [14] is composed of 24 toroidally linked mirrors, each having a 2:1 mirror ratio. The radius of the vacuum vessel is 11 cm in the mirror throats and 25 cm in the mirror midplanes.…”
Section: Description Of the Experimentsmentioning
confidence: 99%
“…The EBT is described in detail in Refs [13,14]. Only facts pertinent to the ICRF heating experiments are presented here.…”
Section: Description Of the Experimentsmentioning
confidence: 99%